What determines the allocation of managerial ownership within firms? Evidence from investment management firms - Dimmock, Stephen G. (2015)
We show that the allocation of managerial ownership to individuals within firms varies depending upon the joint distribution of decision control and decision management rights. Using a unique dataset of institutional investment management firms, we show that ownership is higher for managers: with both executive and operational responsibilities; when benefits of cooperation are higher; and with large contributions to firm value. Consistent with career concerns, we find increases in a manager's ownership are associated with increases in unsystematic risk. Ownership dispersion within the firm is associated with the allocation of monitoring and operational roles and the potential benefits of cooperation.